THE DEVELOPMENT OF THE WEBSITE-BASED HISTORY LEARNING MEDIA "HISTORY GALLERY" FOR TWELFTH-GRADE STUDENTS AT MAN 1 PALU - Denada Rahmadani; Hasan; Amri; Iskandar Ahmad (SOSIOEDUKASI, 2026)
This study aimed to develop a website-based history learning medium, History Gallery, for twelfth grade students at MAN 1 Palu and to examine its feasibility and practicality. The study employed the Research and Development (R&D) method using the ADDIE development model, consisting of the stages of analysis, design, development, implementation, and evaluation. Data were collected through observations, interviews, questionnaires, and documentation. The results showed that the developed learning medium obtained a material expert validation score of 97.3% and a media expert validation score of 86.6%, both categorized as highly feasible. In addition, the teacher response questionnaire yielded a score of 95%, while the students' response questionnaire obtained a score of 83.5%, indicating that the medium was highly practical. The website-based History Gallery facilitated students' understanding of historical content through visual and interactive features, including images, instructional videos, and 360-degree images. These findings indicate that the History Gallery learning medium is both feasible and practical for use in history learning among twelfth-grade students at MAN 1 Palu.